PEMBUATAN SUSU KEDELAI BERKALSIUM TINGGI DENGAN PENAMBAHAN TEPUNG TULANG IKAN KAKAP MERAH (LUTJANUS SANGUINEUS) - Nurjannah Dongoran; Lilik Kustiyah; Sri Anna Marliyati (Media Gizi dan Keluarga, 2007)
The objectives of this research were to study the way to make high calcium soybean milk using red kakap fish bone flour as calcium source. The processing was divided into two main stages, which as protein and fat extraction. The two stages aimed to minimize content protein andfat content on red kakap fish bone flour. Protein extraction was done by boiling with aquades, while the fat exstraction was conducted by using hexane destiller. The addition of red kakap fish bone flour was done on level 0 g (control), 0,92 g, 1,38 g and 1,84 per 240 ml of soybean milk. The addition of calcium on soybean milk made undifferent influence on the acceptance colour, smell, taste, viscosity, and appereance of soybean milk. Nutrition content of soybean milk tended to increase as the greater of red kakap fish bone flour, except for water content. The addition of fish bone fluor influenced significantly on fat, ash, and calcium content, and didn t influenced significantly on water dan protein content. Soybean milk with the addition level of fish bone fluor 1,84 g/240 ml was chosen as the best soybean milk. Soybean milk had acceptance colour, smell, taste, viscosity and appeareance which didn't different with other soybean milk. Meanwhile, soybean milk had relatively high of nutrition content. Soybean milk with calcium availability as 400 mg/240 ml could met about 50%-80% of calcium RDA for vary ages.